Knowledge Sharing and Organizational Support: Keys to Lecturers' Creative Self-Efficacy and Innovation - Ahmad Afan; Gusti Noorlitaria Achmad; Doddy Adhimursandi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In the context of higher education, lecturers' capacity to engage in innovative work behavior is critical to institutional development and academic excellence. This study investigates the role of knowledge sharing and perceived organizational support in enhancing creative self-efficacy and their combined influence on innovative work behavior among university faculty members. This study aimed to develop and test a mediation model in which creative self-efficacy acts as a psychological mechanism linking social-organizational factors to innovation outcomes. Using a quantitative approach, data were collected from 79 lecturers at a state university in Indonesia. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to assess the proposed model. The results show that both knowledge sharing and perceived organizational support significantly predict creative self-efficacy, which in turn directly affects innovative behavior. Furthermore, creative self-efficacy mediates the relationship between the two predictors and innovative behavior. These findings provide theoretical insights into the role of self-efficacy in mediating the social and organizational drivers of innovation. Practically, this study suggests that universities should foster collaborative environments and invest in psychological empowerment to enhance faculty innovation. This study contributes to the advancement of multidimensional innovation models in academic contexts.